Internalisasi Nilai Kesantunan sebagai Dimensi Utama Pengajaran Bahasa dalam Tinjauan Filsafat Ilmu : Internalization of Politeness Values ​​as the Main Dimension of Language Teaching in the Review of Philosophy of Science - Utari, Rini; Sauri, Sofyan (Jurnal Filsafat Indonesia, 2025)
The era of digital disruption has resulted in a decline in the value of language politeness, especially in the context of education. Internalizing the value of politeness in language teaching is a crucial aspect in shaping effective and ethical communication. In the context of philosophy of science, language teaching is not only oriented towards mastering linguistic structures, but also towards the moral and social dimensions contained in language politeness. This study aims to analyze the role of philosophy of science as the basis for internalizing the value of politeness in language teaching. The research method uses a qualitative descriptive approach with literature study data collection techniques. The results showed that the integration of ontology, epistemology, and axiology dimensions in the philosophy of science can provide a comprehensive framework. Philosophy of science-based language teaching not only improves students' technical language skills, but also instills social and moral values. Internalizing language politeness helps students understand the importance of harmonious and empathetic communication. Philosophy of science-based language teaching helps students understand the social context of communication, such as the importance of choosing the right words based on the situation and the interlocutor. In addition, this approach encourages students to think critically about the impact of their communication on others, both in the real and digital worlds. There is a need to strengthen the role of teachers in integrating the value of politeness in the language learning curriculum to create contextual learning. In addition, wise use of technology can strengthen polite language learning that is relevant to the needs of the digital era. This is expected to create a young generation that excels morally and socially.